IMPLEMENTASI PROGRAM BANTUAN PEMERINTAH DALAM UPAYA PENGEMBANGAN WIRAUSAHA PEMULA DI KEMENTERIAN KOPERASI DAN UKM (Studi Pada Kabupaten Lombok Tengah) - Yahya, Mahendra Purnama; Santoso, Bambang; Hariswanto, Alfi (FIA UB, 2018)
This research was motivated by the main problems faced by Small and Medium Enterprises (SMEs) is lack of capital. Refer to Regulations No. 20 of 2008, the Ministry of Cooperatives and SMEs was responsible for empowering SMEs which is through Start-Up Capital Assistances Program for startup Entrepreneur. The aim of the research to analyze and describe the program implementation as well as supporting and inhibiting factors based on the Van Meter and Van Horne policy implementation models. This type of research uses a description method using the qualitative approach. The results show the Implementation of Start-Up Capital Assistances Program for startup Entrepreneur needs to be improved due to lack of communication and and limited resources Â